Pengaruh Bukaan pada Gedung FAD UPN terhadap Efisiensi Energi Menuju Indonesia NZE 2050 - Gian Yeung Ramadhan Sadewa; Heru Prasetiyo Utomo (Universitas Medan Area, 2026)
Carbon emissions have become a major issue in Indonesia’s effort to contribute to a better global environment. As a developing country, Indonesia faces the challenge of reducing carbon emissions while sustaining its ongoing development. One of the largest contributors to the country’s carbon footprint is electricity production through coal combustion. Net-Zero Emission (NZE) is one approach to reduce the amount of carbon released into the atmosphere. This research aims to analyze how building envelopes and openings in an educational building affect natural lighting and heat gain, and to design efficient lighting and air conditioning (AC) systems to minimize energy consumption. The study begins by calculating the Overall Thermal Transfer Value (OTTV) of the building envelope, followed by energy simulations using the Revit Insight plugin. Natural lighting levels are measured using the Velux Daylight Sensor to obtain lux values from each room’s openings. After data collection, alternative and more efficient lighting and AC plans are developed. Results show that existing openings provide sufficient daylighting, while the hottest area is located along the building’s outer edge. Solutions such as solar panels and solar tubes can significantly reduce energy demand. These innovations are expected to be applicable to existing buildings in Indonesia to help lower national carbon emissions.